MODIFIKASI SEPEDA UNTUK ALAT PEMIPIL JAGUNG - Frederik Ponglasak (Faculty of Agriculture, Musamus University, 2021)
The purpose of this study was to test the modified corn sheller tool and the production capacity of the tool. Farmers do corn shelling manually by hand, so it takes a long time. The method used is a modification of a bicycle for corn shellers which can help small-scale corn farmers in the corn shelling process. The corn sheller has the main component in the form of a sheller which functions to peel the corn kernels from the cob, using a gear and chain as a drive that is related to rotating the shell which is done by a person or individual by swinging a bicycle pedal. Tool testing was carried out with 10 repetitions with each shelling using 6 corn cobs. The results showed that the production capacity of modified bicycles for corn shellers from 10 replicates showed that the lowest data was 80.18 kg/hour and the highest data was 91.29 kg/hour. Modification of the bicycle for a corn sheller from 10 repetitions on threshing corn from the cob did not find damage to the corn kernels.